The damage of Chaetophloeus mexicanus (Curculionidae: Scolytinae) to Eysenhardtia polystachya (Fabaceae) stems - Burgos-Solorio, Armando; Terrazas, Teresa (Instituto de Ecología, A.C., 2016)
Damage caused to Eysenhardtia polystachya by the bark beetle Chaetophloeus mexicanus (Coleoptera: Curculionidae; Scolytinae) was investigated as was host response to infestation. A general wood and bark anatomy of E. polystachya is given. Larvae and adults of C. mexicanus penetrate, settle down and consume noncollapsed phloem cells, vascular cambium, and secondary xylem. As a response to damage, there is a deposition of dark-staining contents (tannins) in the cells that limit the cavern. At xylem, this deposition occurs in the lumen of some vessels and fibers, but tissue proliferation did not appear. In the noncollapsed phloem a greater proportion of thick-walled cells and darkstaining contents were observed. However, above of this region, the differentiation of some parenchyma phloematic cells starts. Damage is mainly centered in the noncollapsed phloem, vascular cambium, and the just differentiated xylem cells clearly interrupting water and sap movement.